Umbilical Artery Doppler Velocimetry Along With Uric Acid Values for the Screening of Preeclampsia in Second Trimester of Pregnancy - Shah Gul Khan, Aalia Yousaf, Mahin Saeed, Pareesae Artemis Humayun, Hooria Khan, Ammara Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Preeclampsia is a leading cause of maternal and fetal complications, and early detection is essential for better management. This study aimed to assess the combined utility of umbilical artery Doppler velocimetry and serum uric acid levels for screening preeclampsia during the second trimester. Methodology: Combined Military Hospital Malir Cantonment recruited 60 pregnant women in their second trimester (14–28 weeks) between April 11, 2023, and October 10, 2023. Measurements were taken of uric acid levels and Doppler indices, which include systolic/diastolic ratio [S/D], resistance index [RI], and pulsatility index [PI]. The diagnosis of preeclampsia was made using clinical criteria. Associations were evaluated using statistical techniques such as logistic regression and chi-square testing. Results: Of the 60 participants, 12 (20%) developed preeclampsia. Elevated uric acid (≥5.5 mg/dL) was found in 24 participants (40%). Abnormal Doppler indices were observed in 14 (PI), 10 (RI), and 16 (S/D ratio) participants. However, no significant association was found between abnormal parameters and preeclampsia. The combined screening approach showed 0% sensitivity, 64.3% specificity, and 90% negative predictive value. Conclusion: This study found that neither elevated uric acid nor abnormal Doppler indices effectively predicted preeclampsia in the second trimester. The combined screening approach had limited predictive value. Larger studies are needed to validate these findings and explore other potential biomarkers for early preeclampsia detection. Keywords: Preeclampsia, Second Trimester, Uric Acid, Doppler Velocimetry, Screening, Pregnancy.